Occult cancer detection in venous thromboembolism: the past, the present, and the future. Issue 1 (16th June 2017) - Khan, Faizan; Rahman, Alvi; Carrier, Marc
Abstract: Essentials Unprovoked venous thromboembolism (VTE) may be the first manifestation of an undiagnosed cancer. The rate of occult cancer detection in patients with unprovoked VTE is approximately 5%. Clinicians should keep a low threshold of suspicion for occult cancer in these patients. Patients should only undergo a limited as well as age‐ and gender‐specific cancer screening. Unprovoked venous thromboembolism (VTE) can be the first manifestation of an undiagnosed cancer. Recently published studies have suggested that approximately 4‐5% of patients with new unprovoked VTE will be diagnosed with cancer within 12 months of follow‐up. Therefore, it is important for clinicians to keep a low threshold of suspicion for occult cancer in this patient population. After an unprovoked VTE diagnosis, patients should undergo a thorough medical history, physical examination, basic laboratory investigations (ie, complete blood count and liver function tests), chest X‐ray, as well as age‐ and gender‐specific cancer screening (breast, cervical, colon, and prostate). More intensive cancer screening including additional investigations (eg, computed tomography of the abdomen/pelvis) does not seem to increase the rate of occult cancer detection, decrease cancer‐related morbidity, or increase survival or cost‐effectiveness.